Professionals' Experiences of the Relations between Personal History and Professional Role - Hege Sjølie; Bengt Karlsson; Per-Einar Binder (Hindawi Limited, 2013)
The purpose of this paper is to explore whether and how workers in a crisis resolution home treatment (CRHT) team experience the relationship between their personal history and professional role. This paper is based on 13 in-depth interviews with health professionals working in CRHT. The interviews were analysed using a hermeneutic-phenomenological approach. Participants expressed that there is a relationship between their personal history and professional role, and three themes are highlighted as particularly important in, namely experiences related to the participants as individuals, work-related experiences and family-related experiences. The participants write meaning into the relationship between their personal history and professional role. By relating and exploring their own life stories in the interviews, they work on forming meaning and identity.